Proteomic profiling and characterization of differential allergens in the nematodes Anisakis simplex sensu stricto and A. pegreffii. Issue 12 (21st May 2014) - Arcos, Susana C.; Ciordia, Sergio; Roberston, Lee; Zapico, Inés; Jiménez‐Ruiz, Yolanda; Gonzalez‐Muñoz, Miguel; Moneo, Ignacio; Carballeda‐Sangiao, Noelia; Rodriguez‐Mahillo, Ana; Albar, Juan P.; Navas, Alfonso
<x xml:space="preserve">Abstract</x> The parasite species complex Anisakis simplex sensu lato (Anisakis simplex sensu stricto; (A. simplex s.s.), A. pegreffii, A. simplex C) is the main cause of severe anisakiasis (allergy) worldwide and is now an important health matter. In this study, the relationship of this Anisakis species complex and their allergenic capacities is assessed by studying the differences between the two most frequent species (A. simplex s.s., A. pegreffii) and their hybrid haplotype by studying active L3 larvae parasiting Merluccius merluccius. They were compared by 2D gel electrophoresis and parallel Western blot (2DE gels were hybridized with pools of sera from Anisakis allergenic patients). Unambiguous spot differences were detected and protein assignation was made by MALDI‐TOF/TOF analysis or de novo sequencing. Seventy‐five gel spots were detected and the corresponding proteins were identified. Differentially expressed proteins for A. simplex s.s., A. pegreffii, and their hybrid are described and results are statistically supported. Twenty‐eight different allergenic proteins are classified according to different families belonging to different biological functions. These proteins are described for the first time as antigenic and potentially new allergens in Anisakis. Comparative proteomic analyses of allergenic capacities are useful for diagnosis, epidemiological surveys, and clinical research. All MS data have been deposited in the ProteomeXchange with identifier PXD000662 (http://proteomecentral.proteomexchange.org/dataset/PXD000662).